Political Environment as a Factor of Foreign Investment in Serbia - Ivana; Marjanović, Darko; Lazić, Milena (Serbian political thought, 2023)
The purpose of the paper is to research the influence of political environment factors on the inflow of foreign investments in Serbia. Keeping in mind that many countries in Southeast Europe find themselves in a situation where foreign investments are a necessity and a need for whole economic development, this research focused on Serbia owing to its results in foreign investment attraction during a transition period. Primary data collected using a survey technique on 88 foreign companies that invested in Serbia from 2001 to 2019 were analysed using a quantitative methodology (ANOVA and t-test). The results indicate that the stability of the government and the rule of law are the most important conditions for foreign investors in Serbia. This research’s originality is reflected in the primary data and research results obtained.